The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fnmol.2023.1185883
|View full text |Cite
|
Sign up to set email alerts
|

A single intranasal dose of human mesenchymal stem cell-derived extracellular vesicles after traumatic brain injury eases neurogenesis decline, synapse loss, and BDNF-ERK-CREB signaling

Abstract: An optimal intranasal (IN) dose of human mesenchymal stem cell-derived extracellular vesicles (hMSC-EVs), 90 min post-traumatic brain injury (TBI), has been reported to prevent the evolution of acute neuroinflammation into chronic neuroinflammation resulting in the alleviation of long-term cognitive and mood impairments. Since hippocampal neurogenesis decline and synapse loss contribute to TBI-induced long-term cognitive and mood dysfunction, this study investigated whether hMSC-EV treatment after TBI can prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…23,24 Intranasal (IN) administration of human MSC-derived extracellular vesicles in traumatic brain injury (TBI) mice increases neurogenesis in the sub-ventricular zone (SVZ) by increasing cell proliferation and enhancing the expression of DCX and NeuN. 25 Pourhadi et al also demonstrated that intranasal exosomes reduce amyloid-beta deposits and increase hippocampus preand post-synaptic protein expression to improve spatial memory in Alzheimer's disease model. 26 Based on the above, we aimed to investigate the impact of intravenous exosome delivery on cognitive function and neurogenesis markers in the DG and CA1 region of the hippocampus in METHtreated mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Intranasal (IN) administration of human MSC-derived extracellular vesicles in traumatic brain injury (TBI) mice increases neurogenesis in the sub-ventricular zone (SVZ) by increasing cell proliferation and enhancing the expression of DCX and NeuN. 25 Pourhadi et al also demonstrated that intranasal exosomes reduce amyloid-beta deposits and increase hippocampus preand post-synaptic protein expression to improve spatial memory in Alzheimer's disease model. 26 Based on the above, we aimed to investigate the impact of intravenous exosome delivery on cognitive function and neurogenesis markers in the DG and CA1 region of the hippocampus in METHtreated mice.…”
Section: Introductionmentioning
confidence: 99%
“…They also offer protection to the nervous system against oxidative damage in several neurological diseases 23,24 . Intranasal (IN) administration of human MSC‐derived extracellular vesicles in traumatic brain injury (TBI) mice increases neurogenesis in the sub‐ventricular zone (SVZ) by increasing cell proliferation and enhancing the expression of DCX and NeuN 25 . Pourhadi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, normalized neurogenesis in LPS-treated mice receiving hiPSC-NSC-EVs is likely a downstream beneficial effect of EVs suppressing neuroinflammation. However, involvement of pro-neurogenic pathways, such as the activation of brain-derived neurotrophic factor-extracellular signal-regulated kinase-cyclic AMP response-element binding protein signaling, as observed in a traumatic brain injury model following the administration of human bone marrow mesenchymal stem cell-derived EVs, cannot be ruled out [ 48 ]. Such possibility is supported by hiPSC-NSC-EVs exhibiting enriched payload of proteins such as agrin efficient in promoting CREB activation [ 89 ] and agrin and PTX3 capable of directly enhancing neurogenesis [ 90 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have detailed immunohistochemical methods employed in this study [ 35 , 48 , 49 ]. In each animal, every 15th or 20th section through the whole hippocampus was processed for immunohistochemical identification of IBA-1 + microglia, GFAP + astrocytes, BrdU-positive newly born cells and doublecortin (DCX) positive newly generated neurons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation